Figur Pemimpin Ideal Dalam Islam Perspektif Dosen IAIN Kudus - Rochanah, Rochanah rochanah (POLITEA, 2019)
This research is a research with a qualitative approach through descriptive-analytical methods. The technique of collecting data through observation, interviews and documentation. The urgency of this study is to find out more about how ideal leaders in Islam are in the view of academics (lecturers) who should have enough observant and critical thinking in choosing a leader. The problem that the researchers raised in this study was; how is the ideal leader figure in Islam the perspective of the Holy IAIN lecturer? The results showed that the ideal leader figure in Islam was the perspective of the Holy IAIN lecturer as a trustworthy leader, a fair leader, a leader who promoted deliberation (shura), a leader who enforced amr ma'ruf nahi munkar, protecting the people, a leader who provided employment, leaders who pay attention to the welfare of honorary teachers, wise leaders regarding the rules of finger print.